1996
DOI: 10.1074/jbc.271.37.22746
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Cis-acting Negative Regulatory Element Affecting Expression of the CYP1A1 Gene in Rat Epidermal Cells

Abstract: Polycyclic aromatic hydrocarbons such as 3-methylcholanthrene are toxic to rat epidermal cells in low passages (3 to 6), but cultures of high passage ( 15)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…This is associated with differentiation at high passage numbers concomitant with down-regulation of Cyp1A1 and Cyp1B1 (27). A sequence similar to half of this element is found in the mouse Cyp1B1 region immediately downstream of the enhancer element in a position equivalent to the Cyp1A1 element (27). This cis-acting element is distinct from the negative regulatory element described for the CYP1A1 5Ј-flanking region by Hines and co-workers (59,60).…”
Section: Table Imentioning
confidence: 82%
See 3 more Smart Citations
“…This is associated with differentiation at high passage numbers concomitant with down-regulation of Cyp1A1 and Cyp1B1 (27). A sequence similar to half of this element is found in the mouse Cyp1B1 region immediately downstream of the enhancer element in a position equivalent to the Cyp1A1 element (27). This cis-acting element is distinct from the negative regulatory element described for the CYP1A1 5Ј-flanking region by Hines and co-workers (59,60).…”
Section: Table Imentioning
confidence: 82%
“…The inhibitory region located between Ϫ210 and Ϫ432 also contained the minor start site (Ϫ332), two XREs, an E-box, and a putative SP-1 site (18-base G-rich sequence, G 6 TG 6 TG 4 ). A negative cis-acting regulatory element has been identified for the Cyp1A1 gene in rat epidermal cells (27). This is associated with differentiation at high passage numbers concomitant with down-regulation of Cyp1A1 and Cyp1B1 (27).…”
Section: Table Imentioning
confidence: 99%
See 2 more Smart Citations
“…Our studies clearly demonstrated that the TCDD-dependent induction of Cyp1a-1 was suppressed in these tumors but not the adjacent normal epidermis. Recent studies from Denison's laboratory suggest that CYP1A1 induction in rat keratinocytes is modulated by the interaction of a trans-acting factor or factors with a negative regulatory element proximal to the CYP1A1 transcription start site [34]. Whereas processes initiated at this element suppress CYP1A1 induction, they do not disrupt ligand-induced AHR transformation or DRE binding [34].…”
Section: Discussionmentioning
confidence: 99%